Forms of vitality play and symbolic play during the third year of life - Español, Silvia Ana (2015)
This article focuses on the development of forms of vitality play, a recently described type of play, and links it to the development of symbolic play, one of the most studied types of play in developmental psychology. Two adult–infant dyads were videotaped longitudinally during in-house free play meetings every 15 days during the third year of life. Convergence technique was applied in order to accelerate the longitudinal study. A total of 17 h 48 min were registered in 28 sessions. An observational code with categories of forms of vitality play (a non-figurative play frame in which child and adult play together with the dynamics of their own movements and sounds in a repetition–variation form), symbolic play, and categories of combined patterns of both types of play was applied. The rate of each play was calculated for different age periods. Forms of vitality play is present at a constant rate during the third year of life. Symbolic play flourishes during this period. Combined play patterns are not the most frequent but are present from the beginning to the end of the third year. We suggestthat FoVP favours intimate and intersubjective experiences essential to the understanding and the development ofthe interpersonal world;thatit can be thought of as a good runway for the development of symbolic play; and that it prepares the child to participate in the temporal arts that belong to his culture.